The constitution's text in foreign affairs - Ramsey, Michael D., 1964- (Harvard University Press, 2007)
Ramsey describes the constitutional law of foreign affairs derived from an historical understanding of the Constitution's text. Examining recurring foreign affairs controversies such as the power to enter armed conflict, the author shows how the words, structure, and context of the Constitution can resolve pivotal court cases and modern disputes.